FURTHER EVIDENCE ON THE VALIDITY OF THIRLWALL’S LAW - Leon Podkaminer (Zeszyty Naukowe Wyższej Szkoły Finansów i Prawa w Bielsku-Białej)
A simple equation is considered whose empirical analysis could confirm – or reject – the validity of Thirlwall’s Law. Autoregressive Distributed Lags (Bounds) approach is used to establish the empirical adequacy of the Law. The analysis, working with data for 58 countries and covering the years 1960-2012, suggests that the Law may not hold for the decisive majority of countries considered.